(untitled) (Fiep Bulletin - online, 2011)
This research describes experiences through specific physical activities in a group. Capoeira is a traditional Brazilian physical activity that evolves group work, self-defense, dance, acrobatics, music and musical instruments. Four elements developed by Van Manen (1990) were used for exploring the experiences: body as corporeal and mental experiences, time as the situatedness and the sense of passing time, space as the physical environment, and human relations related to the interaction with others. The phenomenology was the philosophical and methodological principle. According to Heidegger (2000), it considers that researchers should be conscious for the hidden elements inside people’s everyday experiences (p.123). In this qualitative study, eighty people attended regular capoeira lessons. Non-structured interviews were applied to fifteen randomized participants. The result indicated lived time as significant for the experience and participants realized bad and good aspects of life co-existing in a social setting. In this sense, participants evaluated that lived body, lived time, lived space and lived human relation brought an intrinsic balance between positive and negative elements along the practice of capoeira, as a normal consequence of living in a group, and it may offer an optimum space for coping and problem solving.